Semi-Automated Recording of Facial Sensitivity in Rat Demonstrates Antinociceptive Effects of the Anti-CGRP Antibody Fremanezumab - Nicola Benedicter; Karl Messlinger; Birgit Vogler; Kimberly D. Mackenzie; Jennifer Stratton; Nadine Friedrich; Mária Dux (MDPI AG, 2023)
Migraine pain is frequently accompanied by cranial hyperalgesia and allodynia. Calcitonin gene-related peptide (CGRP) is implicated in migraine pathophysiology but its role in facial hypersensitivity is not entirely clear. In this study, we investigated if the anti-CGRP monoclonal antibody fremanezumab, which is therapeutically used in chronic and episodic migraines, can modify facial sensitivity recorded by a semi-automatic system. Rats of both sexes primed to drink from a sweet source had to pass a noxious mechanical or heat barrier to reach the source. Under these experimental conditions, animals of all groups tended to drink longer and more when they had received a subcutaneous injection of 30 mg/kg fremanezumab compared to control animals injected with an isotype control antibody 12-13 days prior to testing, but this was significant only for females. In conclusion, anti-CGRP antibody, fremanezumab, reduces facial sensitivity to noxious mechanical and thermal stimulation for more than one week, especially in female rats. Anti-CGRP antibodies may reduce not only headache but also cranial sensitivity in migraineurs.